2024
DOI: 10.1038/s41598-024-53384-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between alkaline phosphatase to albumin ratio and mortality among patients with sepsis

Shuyue Liu,
Kai Zhao,
Chunhong Shao
et al.

Abstract: The alkaline phosphatase-to-albumin ratio (APAR) is correlated to worse prognosis in coronary artery disease, cancer, and acute renal failure. However, the relationship between APAR and sepsis prognosis has received little research. The content of this research was to investigate the prognostic relationship between APAR and sepsis. And validate the stability of the correlation in 90-days and 1-year mortality. Retrospective cohort research was conducted basing MIMIC-IV database (version 2.0). The hazard ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, a study conducted by Liu et al demonstrated that APAR was independently associated with mortality in patients with sepsis [14]. Moreover, higher APAR levels were independently associated to increased cancer mortality as reported, including lung cancer [7,8,11], hepatocellular carcinoma [6], pancreatic ductal adenocarcinoma [9,20], nasopharyngeal carcinoma [12], urothelial carcinoma [13], and some other types [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 97%
“…The ALP-to-ALB ratio (APAR), a novel prognostic marker amalgamating ALP and ALB, has been proposed and exhibits promising prognostic value in various cancers and other diseases [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Moreover, APAR exhibits superior predictive performance for clinical outcomes when compared with independent ALP and ALB measurements [20].…”
Section: Introductionmentioning
confidence: 99%